Geographical analysis of health facilities in port Har-court city local government area, rivers state, Nigeria a case study of rivers state, Nigeria - Menegbo, Emmanuel (International Journal of Advanced Geosciences, 2017)
One of the Millennium Development Goals (MDGs) which 2015 was the target date for its achievement now sustainable goal is stopping the spread of diseases that are preventable. GIS measures coverage, access and pattern's utilization of healthcare services and is important in the research, management, and planning of Healthcare facilities and system. This work, therefore, investigates the spatial distributions of healthcare facilities in Port Harcourt city LGA in Rivers State, Nigeria. Primary data was acquired using GPS handheld receiver and Secondary data such as the attribute (population data, names of hospitals) and spatial data (administrative map, road, and settlement) obtained from government official records. Data obtain shown on a map the spatial distributions of health facilities and access road to the facilities. The result also depicts a spatial distribution's pattern of healthcare facilities and thus insight gain in access to healthcare facilities and services in the LGA.